1991
DOI: 10.1007/bf01690765
|View full text |Cite
|
Sign up to set email alerts
|

Severe falciparum malaria (21 cases)

Abstract: The incidence of severe falciparum malaria is increasing in the developed countries and mortality remains high despite progress in intensive care management and schizonticide treatment. Many authors emphasize the importance of exchange transfusion (EXT) in the most severe cases. We studied 21 cases (34 +/- 12 years, 6 females; SAPS: 8.4 +/- 3.7) of severe malaria (according to WHO criteria) consecutively admitted to ICU between 1985 and 1990: 3 patients underwent EXT. Twenty were febrile above 39 degrees C, 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 34 publications
2
38
1
Order By: Relevance
“…3). Frequently associated complications were reported to be present (median 檄 3), and in four patients, ARDS developed following admission, a pattern similar to that seen with falciparum malaria (128)(129)(130). Logistic regressions in limited case series indicated positive and independent associations with parasitemia and neutrophilia and an inverse association with hemoglobin concentrations at admission (33,43).…”
Section: Complicated Knowlesi Malariamentioning
confidence: 66%
“…3). Frequently associated complications were reported to be present (median 檄 3), and in four patients, ARDS developed following admission, a pattern similar to that seen with falciparum malaria (128)(129)(130). Logistic regressions in limited case series indicated positive and independent associations with parasitemia and neutrophilia and an inverse association with hemoglobin concentrations at admission (33,43).…”
Section: Complicated Knowlesi Malariamentioning
confidence: 66%
“…Hyperparasitaemia was common in these patients. Although the benefit of exchange transfusion over the treatment with antimalarial drug alone remains controversial (Marix 1989), most literature reports satisfactory results in patients who received exchange transfusion (Ahlqvist 1989;Looaresuwan et al 1990;Malin et al 1990;Salord et al 1991;Beards et al 1994;Wilkinson et al 1994). We therefore used exchange transfusion as the adjunct to quinine therapy in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…the mortality exceeded 50% in patients with parasitaemia > 500,000/碌l (Field & Niven 1937). Exchange transfusion used as the adjunct to the antimalarial drugs rapidly reduces parasitaemia (Looaresuwan et al 1990;Salord et al 1991). Parasitized red cells are more rigid and less deformable than unparasitized red cells (Cranston et al 1984;Ahlqvist 1989).…”
Section: Introductionmentioning
confidence: 99%
“…It is concluded that noncardiogenic pulmonary edema in P. falciparum malaria may induce severe respiratory insufficiency [1,3,15]. However, this complication is not necessarily fatal if recognized early and treated promptly.…”
Section: Discussionmentioning
confidence: 99%